Freeing the natural voice : Imagery and Art in the Practice of Voice and Language - Linklater, Kristin (Drama Publishers, 2006)
Freeing the Natural Voice presents a lucid and multi-leveled account of the human voice in the context of performance. The emphasis of the work is on the removal of the physical and psychological blocks that inhibit the human vocal instrument and its objective is a voice in direct contact with emotional impulse, shaped by the intellect but not restricted by it. Its logical progression of exercises is designed for students, teachers, professionals, and anyone interested in vocal expression.